Takeovers, Shareholder Returns, and the Theory of the Firm - Firth, Michael (Quarterly Journal of Economics, 1980)
The paper examines recent merger and takeover activity in the United Kingdom. Specifically, the impact of takeovers on shareholder returns and management benefits is analyzed, and some implications for the theory of the firm are drawn from the results. The research showed that mergers and takeovers resulted in benefits to the acquired firms' shareholders and to the acquiring companies' managers, but that losses were suffered by the acquiring companies' shareholders. The results are consistent with takeovers being motivated more by maximization of management utility reasons, than by the maximization of shareholder wealth.